AGROCHEMICAL ASPECTS OF FORMATION OF HIGH YIELDS OF GRAIN CROPS IN THE CENTRAL NECHERNOZEMIE - V. V. Kononchuk (Зерновое хозяйство России, 2018)
The article considers the results of 10-year research of the optimization of the fertilizing system of winter and spring crops in the crop rotations on the sod-podzolic soils of the Central Nechernozemie in Russia. It has been shown that it is necessary to produce and support a high level of movable phosphorus and potassium on the background of a weakly acidic or almost neutral response of soil solution to obtain grain productivity of the present varieties of winter wheat, rye and barley (selected in the Moscow RIA “Nemchinovka”) in the amount of 6-8 t/ha, 5-6 t/ha and 4 t/ha respectively in the arable (0-30 sm) soil layer at the beginning of vegetation period in spring. At the same time availability of nitrogen in the soil layer (0-60sm) should not be less than 65-80% in comparison with its availability in the future yield. When calculating the nitrogen dose for the early spring fertilizing of winter wheat and spring crops it is necessary not only to be aware and take into account the actual and optimal availability of the element in the soil and plants at the beginning of the vegetation period, but also to use the effect of the amounts of nitrogen consumption, determined during the study, on the shift of amount of N-NO3 in the layer and the content of Nt per plant.